‘A Shared Reality between a Journalist and the Audience’: How Live Journalism Reimagines News Stories - Ruotsalainen Juho; Villi Mikko (Cogitatio Press, 2022)
Live journalism is a new journalistic genre in which journalists present news stories to a live audience. This article investigates the journalistic manuscripts of live journalism performances. With the focus on texts, the article reaches beyond the live performance to explore the wider implications and potentials pioneered by live journalists. The data were gathered from Musta laatikko (‘Black Box’) manuscripts, a live journalism production by the Finnish newspaper Helsingin Sanomat. The manuscripts were analysed as eudaimonic journalism through four conceptual dimensions: self-transcendence, autonomy, competence, and relatedness. The results show how eudaimonic journalism can contemplate history, the future, and the meaning of finite human life. Moreover, by describing self-determinant individuals and communal social relationships, eudaimonic news stories can foster a sense of meaning and agency in audience members. By employing eudaimonia, journalists at large can reflect on the meaning and purpose of contemporary life and offer a more comprehensive understanding of the world. Such understanding includes not only facts and analysis, but also values, affects, and collective meanings mediated through the subjectivity of a journalist